Organic-carbon deposition in the Cretaceous of the Ionian Basin, NW Greece: the Paquier Event (OAE 1b) revisited - Tsikos, H; Karakitsios, V; van Breugels, Y; Walsworth-Bell, B; Bombardiere, L; Petrizzo, M; Sinninghe Damsté, J; Schouten, S; Erba, E; Silva, I; Farrimond, P; Tyson, R; et al. (Cambridge University Press, 2004)
We present new stable (C, O) isotopic, biostratigraphic and organic geochemical data for the Vigla Shale Member of the Ionian Zone in NW Greece, in order to characterize organic carbon-rich strata that potentially record the impact of Cretaceous Oceanic Anoxic Events (OAEs). In a section exposed near Gotzikas (NW Epirus), we sampled a number of decimetre-thick, organic carbon-rich units enclosed within marly, locally silicified, Vigla Limestone (Berriasian-Turonian). All these units are characterized by largely comparable bulk geochemical characteristics, indicating a common marine origin and low thermal maturity. However, the stratigraphically highest of these black shales is further distinguished by its much higher total organic-carbon (TOC) content (28.9 wt%) and Hydrogen Index (HI) (529), and much enriched δ13C org value (-22.1‰). Planktonic foraminiferal and calcareous nannofossil biostratigraphy indicate a lower to middle Albian age for the strate immediately above, and a lower Aptian age for the strata below, the uppermost black shale. In terms of molecular organic geochemistry, the latter black shale is also relatively enriched in specific isoprenoidal compounds (especially monocyclic isoprenoids), whose isotopic values are as high as -15%, indicating a substantial archael contribution to the organic matter. The striking similarities between the molecular signatures of the uppermost Vigla black shale and coeval organic-rich strata from SE France and the North Atlantic (ODP Site 1049C) indicate that this level constitutes a record of the Paquier Event (OAE 1b).